2021
DOI: 10.1177/19714009211026904
|View full text |Cite
|
Sign up to set email alerts
|

Chronic subdural hemorrhage predisposes to development of cerebral venous thrombosis and associated retinal hemorrhages and subdural rebleeds in infants

Abstract: For infants presenting with subdural hemorrhage, retinal hemorrhage, and neurological decline the “consensus” opinion is that this constellation represents child abuse and that cerebral venous sinus thrombosis and cortical vein thrombosis is a false mimic. This article contends that this conclusion is false for a subset of infants with no evidence of spinal, external head, or body injury and is the result of a poor radiologic evidence base and misinterpreted data. Underdiagnosis of thrombosis is the result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
(204 reference statements)
0
4
0
Order By: Relevance
“…However, subdural hemorrhage, injury to the posterior region of the head or occipital lobe, a Glasgow coma score (GCS) below 15, convulsive episodes and vomiting have been suggested to be fairly reliable predictors of retinal hemorrhage [4,5]. Nevertheless, clinicians are expected to be wary of pitfalls with regard to this delicate issue, as the co-occurrence of subdural and retinal hemorrhage cannot irrefutably indicate AHT, when there is precedent that such clinical picture might be suggestive of life-threatening conditions such as cerebral venous sinus thrombosis, which falls within the category of coagulopathies [6]. In the case of younger children or infants, the situation is substantially more complicated because retinal hemorrhage in infants often occurs secondary to an underlying intracranial pathology of unknown origin [7].…”
Section: Retinal Hemorrhage In Childrenmentioning
confidence: 99%
“…However, subdural hemorrhage, injury to the posterior region of the head or occipital lobe, a Glasgow coma score (GCS) below 15, convulsive episodes and vomiting have been suggested to be fairly reliable predictors of retinal hemorrhage [4,5]. Nevertheless, clinicians are expected to be wary of pitfalls with regard to this delicate issue, as the co-occurrence of subdural and retinal hemorrhage cannot irrefutably indicate AHT, when there is precedent that such clinical picture might be suggestive of life-threatening conditions such as cerebral venous sinus thrombosis, which falls within the category of coagulopathies [6]. In the case of younger children or infants, the situation is substantially more complicated because retinal hemorrhage in infants often occurs secondary to an underlying intracranial pathology of unknown origin [7].…”
Section: Retinal Hemorrhage In Childrenmentioning
confidence: 99%
“…Cortical vein thrombosis (Figure 4) has traditionally been regarded as an important sign of AHT, where the proposed mechanism is a trauma leading to bridging vein rupture/damage, followed by a formation of blood clot/thrombosis 37 . In a recent study, however, Vaslow 38 reported several infants with chronic SDH and cortical vein thrombosis. This again was associated with retinal hemorrhage and neurological decline, leading the authors to question the supposed connection between cortical vein thrombosis and AHT.…”
Section: Other Findingsmentioning
confidence: 99%
“…Various types of intracranial hematomas, as well as intraventricular hematomas and brain tissue contusions, can occur from injury to the cerebrovasculature in the affected areas. These particulate lesions can cause a mass effect, as well as an upsurge in ICP and brain herniation [ 17 , 65 , 67 , 68 ]. As a primary injury, brain laceration may predispose the sufferer to convulsions and epilepsy [ 69 , 70 ].…”
Section: Mechanism Of Abimentioning
confidence: 99%